A Linkage between Personal Characteristics and Entrepreneurial Behavior in the Malaysian Public Sector - Liyana Mohd Kamil, Nurul; Abdul Rahman, Abdullah; Robert, Christine (International Journal of Engineering and Technology, 2018)
Entrepreneurial behavior within an organization is deemed relevant as an instrument to foster organizational growth, develop a strategic vision and create an energetic work environment because of its valuable impact on the performance of service. Beneficial display of entrepreneurial behavior by organizational members contributes to the venture significant of an organization. Although multiple kinds of research suggest the importance of individual entrepreneurial behavior in organizations, an empirical study on its predictors, particularly within the public sector is still infancy. Thus, the paper aims to provide an integrated review of the role of personal characteristics (in the form of entrepreneurial leadership, self-efficacy, and career adaptability) on entrepreneurial behavior among Malaysian public sectorâ€™s managers, which could subsequently exhibit the performance of the excellent services.Â Â